Repurposing topical triclosan for cutaneous leishmaniasis: Preclinical efficacy in a murine Leishmania (L.) amazonensis model. Issue 2 (6th August 2020) - Mesquita, Juliana Tonini; Romanelli, Maiara Maria; de Melo Trinconi Trinconi CM, Cristiana; Guerra, Juliana Mariotti; Taniwaki, Noemi Nosomi; Uliana, Silvia Reni Bortolin; Reimão, Juliana Quero; Tempone, Andre Gustavo
Abstract: Leishmaniasis remains an important neglected tropical infection caused by the protozoan Leishmania and affects 12 million people in 98 countries. The treatment is limited with severe adverse effects. In the search for new therapies, the drug repositioning and combination therapy have been successfully applied to neglected diseases. The aim of the present study was to evaluate the in vitro and in vivo anti‐ Leishmania ( Leishmania ) amazonensis potential of triclosan, an approved topical antimicrobial agent used for surgical procedures. in vitro phenotypic studies of drug‐treated parasites were performed to evaluate the lethal action of triclosan, accompanied by an isobolographic ex‐vivo analysis with the association of triclosan and miltefosine. The results showed that triclosan has activity against L. ( L. ) amazonensis intracellular amastigotes, with a 50% inhibitory concentration of 16 μM. By using fluorescent probes and transmission electron microscopy, a pore‐forming activity of triclosan toward the parasite plasma membrane was demonstrated, leading to depolarization of the mitochondrial membrane potential and reduction of the reactive oxygen species levels in the extracellular promastigotes. The in vitro interaction between triclosan and miltefosine in the combination therapy assay was classified as additive against intracellular amastigotes. Leishmania ‐infected mice were treated with topical triclosan (1% base cream for 14 consecutive days), and showed 89% reduction in the parasite burden. The obtained results contribute to the investigation of new alternatives for the treatment of cutaneous leishmaniasis and suggest that the coadministration of triclosan and miltefosine should be investigated in animal models.